Decentralized Cooperation Effect on Local Investment Analysis : Case Study of Collines Department in Benin - Hounmenou, Bernard G. (DEMO, 2020)
Decentralized cooperation constitutes a territory to territory cooperation which registers for a local development dynamic. If it is largely admitted that this kind of cooperation contributes positively to local development resources mobilization for southern partners, number of analyzers feel that those contributions are weak. Through the analysis of experiences of the former Picardie Region (France) and Collines Department (Benin), this paper studies the effect of decentralized cooperation on local investment. In studied context, only central government subsidies have a significant positive incidence on such investment.(original abstract)